Language learning strategies in grammar: A comparative study between good and poor learners in UiTM Pahang / Kamisah Ariffin, Misyana Susanti Husin and Roselina Musahar - Ariffin, Kamisah; Husin, Misyana Susanti; Musahar, Roselina (2004)
There are differences in UiTM students' performance in English, notably grammar. Some students perform significantly better than others who receive the same amount of instructions in the language. O'Malley and Chamot (1990) on their studies on students' performance in the second language have proven that learners do apply strategies to cope with the difficulties presented by the second language, that 'competent individuals are effective because of special ways of processing information.' The understanding of what learners 'do' during the stages of learning the language can give indication as to why their linguistic profile has taken place, thus, deserves a careful investigation. This is because for the language instructors, frequent failure after years of language study has led to disappointment and frustrations or even anger at the colossal time spent on teaching. For the students, this may lead to the feeling of inferiority which may eventually lead to negative attitudes towards the language. In the light of the examination and comparison of the strategies, we may consider ways to improve the students' level of performance in grammar and to suggest the planning for more effective and instructional practice for the language instructors.